ACTN3 genotype in professional sport climbers - Ginszt, M.; Michalak-Wojnowska, M.; Gawda, P.; Wojcierowska-Litwin, M.; Korszen-Pilecka, I.; Kusztelak, M.; Muda, R.; Filip, A. A.; Majcher, P. (The Journal of Strength and Conditioning Research, 2018)
The functional RR genotype of the alpha-actinin-3 (ACTN3) gene has been reported to be associated with elite sprint/power athlete status. Although large and rapidly increasing number of studies have investigated the associations between the ACTN3 genotypes and athletic performance in various sport disciplines, there is a lack of studies on the genetic predisposition in sport climbing, which was selected to be part of the next Summer Olympic Games in Tokyo 2020 with three subdisciplines ("lead climbing," "speed climbing," and "bouldering"). The aim of the study is to determine the frequency distribution of ACTN3 genotypes and alleles in professional lead climbers and boulderers. 100 professional sport climbers from Poland, Russia, and Austria were divided into 2 equal groups: professional boulderers and professional lead climbers were involved in the study. ACTN3 allele frequencies and genotypes were compared with 100 sedentary controls. Genotypes were determined using polymerase chain reaction-restriction fragment length polymorphism method. The percent distribution of RR genotype in the boulderers was significantly higher than in lead climbers and controls (62 vs. 26%; 33%, respectively; x2 = 17.230, p = 0.0017). The frequencies of ACTN3 R allele in boulderers differed significantly from lead climbers and controls (77 vs. 51%; 58%, respectively; x2 = 15.721, p = 0.0004). The proportion of the ACTN3 RR genotype is significantly higher in boulderers than in lead climbers and may be related to the specific type of predisposition to this subdiscipline.